Implementation English Teacher’s Creativity in Transition Period at Junior High School - Tresna, Kadek Wahyu (Universitas Pendidikan Ganesha, 2023)
Implementation of face-to-face learning during the transition period makes students confused and tends to be passive when carrying out learning in class. That was because previous learning was carried out online and tended not to run effectively so it was necessary to apply teacher creativity in the classroom to increase student understanding and activity. This study aimed to analyze how teachers implement their creativity towards face-to-face learning during the post-pandemic transitional period. Embedded mixed methods were used as a research design where qualitative data became the main data while quantitative data were used as supporting data. The English teacher in junior high school is choosen as the research subject. Data collection are using self-rated questionnaire, classroom observation, and in-depth interview. For the data analyze technique the researcher assess by assigning a point to each statement on the sheet of observations. The results of the study show that 1) Teachers tend not to meet the criteria of being creative teachers in implementing learning during the transition period where teachers fall into the unlikely creativity category in implementing creativity. Teachers who tend to be uncreative can make students more passive and difficult to understand learning in class, especially during the transition period where students who previously learned less effectively through online platforms are now switching to face-to-face learning which requires them to understand the subject matter well.